Burden of occupational morbidity from selected causes in the United States overall and by NORA industry sector, 2012: A conservative estimate. Issue 12 (14th September 2019) - Groenewold, Matthew; Brown, Linda; Smith, Emily; Haring Sweeney, Marie; Pana‐Cryan, Rene; Schnorr, Theresa
Abstract: Background: Timely and reliable national estimates of the occurrence of occupational injury and illness are needed to monitor the burden of occupational morbidity and mortality, establish research and intervention priorities, and evaluate the progress and effectiveness of prevention efforts. Methods: We provide updated estimates of morbidity from occupational injuries and selected illnesses, using current general population incidence rates, the proportion of the general public with a particular workplace exposure, and the relative risk of illness from that exposure. We provide estimates for the total U.S. working population and for specific industry sectors. Results: We estimate that, in 2012, between 5 712 362 and 5 961 620 total occupational cases, including 0.7 to 1.0 million incident illnesses and 5.0 million injuries, occurred in the United States. Conclusion: The variety of disparate data sources and methods required to compile these estimates highlight the need for more comprehensive and compatible occupational health surveillance in the United States.